Low‐cost triboelectric sensor for speed measurement and weight estimation of vehicles. Issue 8 (17th August 2018) - Yadav, Deepshikha; Azad, Puneet
Abstract : This study presents and tests the accuracy of a low‐cost triboelectric sensor for speed measurement and weight estimation of passenger vehicles in motion. Polytetrafluoroethylene and aluminium films are employed as sensing elements for generating voltage pulses due to movement of vehicles in real time. A number of road tests by 880 and 1020 kg cars in the speed range from 10 to 60 kmph show that the sensor is effective for measuring speeds with more than 95% accuracy and 3% mean absolute percentage error. For weight estimation, it is found that the voltage signals obtained from sensor due to impact between the tires of the vehicles and sensor varies linearly with speed ensuring the reliability of the sensor. On road experimental results reveal that the weight can be predicted from voltage signals by maintaining a database of different class of vehicles. The results and the overall concept indicate that the triboelectric sensor and associated wireless setup is promising for smart traffic‐monitoring applications at a very low cost.